The wish giver : three tales of Coven Tree - Brittain, Bill.; Glass, Andrew, 1949- (New York : HarperTrophy, 1986)
When a strange little man comes to the Coven Tree Church Social promising he can give people exactly what they ask for, three young believers-in-magic each make a wish that comes true in the most unexpected way.
Prologue: the strange little man -- Jug-a-rum -- The tree man -- Water, water, everywhere -- Epilogue: at Stew Meat's store.
"Trophy Newbery"--Cover.
Elem. School Library Collection
Wilson's Children
Wilson's Junior High School
Bulletin (Center for Children's books), October 2008
Elem. School Library Collection, June 2000
Keywords: Magic -- Fiction; Wishes -- Fiction; Magic -- Fiction; Wishes -- Fiction